SWOT Influence Analysis as a Strategy to Increase Competitiveness Based on Sharia Principles (Study at PT BPRS Artha Madani Cikarang Branch) - Rizqi Renaldy; Muhammad Al Mighwar (ORGANIZE: Journal of Economics, Management and Finance, 2025)
Sharia People's Financing Banks (BPRS) in an effort to grow their existence in the banking world are experiencing quite rapid progress, especially in providing services to small and medium and micro businesses, because apart from using sharia principles, BPRS are also considered to be flexible and take a personal approach to their financing model. This study aims to find out how to analyze the influence of SWOT as a strategy to increase competitiveness and its obstacles at PT BPRS Artha Madani KCP Cikarang. In this study using a qualitative descriptive method using a SWOT analysis taken from various aspects. The results of the analysis show that the strengths (strengths) are more dominant than the weaknesses (weaknesses) owned by PT BPRS Artha Madani KCP Cikarang. Likewise, the opportunity factor (Opportunities) is also more dominating than the threat factor (Thearts). Thus PT BPRS Artha Madani KCP Cikarang has the potential to increase strong competitiveness with other banking institutions, both with non-bank institutions and other commercial banks in Bekasi Regency and its surroundings.